Il “ragionevole accomodamento” nella giurisprudenza italiana in materia ecclesiastica* (Stato, Chiese e pluralismo confessionale, 2024)
The “reasonable accommodation” in Italian jurisprudence in ecclesiastical mattersABSTRACT: With judgment n. 24414/2021, the United Sections of the Supreme Court suggested “reasonable accommodation” as a key to resolving conflicts over religious symbols in public school classrooms. This approach, which is typically used to promote equality for workers with disabilities, has been applied to this dispute in a novel way. This paper intends to reconstruct the Court’s proposal of a “reasonable accommodation” model after analyzing the original features of this approach. From the investigation of nature and the application of “reasonable accommodation” in the decision of the Court, this work seeks to verify whether this model can be effectively and legally relevantly applied in the public school context.SOMMARIO: 1. Il crocifisso e l’inedita chiave di risoluzione dei conflitti dopo la sentenza n. 24414 delle Sezioni Unite della Corte di cassazione - 2. La natura del principio del “ragionevole accomodamento” - 3. Il “ragionevole accomodamento” come metodo “mite” - 4. Limiti e prospettive - 5. Brevi osservazioni conclusive.